Bombay phenotype Oh blood group: two case reports. Acute puerperal uterine inversion and term pregnancy in labour - Devabhaktuni, Pratibha; Ponnuru, Malati; Kalattoor, Vijaya Reddy; Palakodeti, Nirupama (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Mrs. A, 30 years, para 3 with three live children was an unbooked emergency admission on 6 April 2007 with history of severe postpartum haemorrhage (PPH). She was in a state of shock with hypotension, tachycardia, pallor due to anaemia. Examination revealed the uterine inversion, uterus visible as a fleshy red mass protruded outside the vaginal introitus. Puerperal uterine inversion was reduced by vaginal manual reposition under observation through a mini laparotomy incision. She was transfused 4 units of O positive blood. On the second postoperative day she had signs and symptoms of a haemolytic transfusion reaction (HTR). She developed jaundice, haematuria and worsening anaemia. She was later detected to be Bombay Oh phenotype. Total 6 units of Bombay phenotype blood was transfused in a couple of days. Case 2: Mrs. R, 22 years primigravida, term gestation was admitted in labour in government maternity hospital/Osmania medical college, Hyderabad on 26 July 2007. A resident from Mahaboob Nagar district of Andhra Pradesh, unbooked emergency admission in labour, had severe anaemia with 4 gms Hb%. Her blood group was diagnosed as Bombay phenotype. She was given a vaginal delivery and transfused with compatible Oh Bombay blood obtained from Red Cross, Warangal, Andhra Pradesh.